Pembuatan Shampo Berbahan Baku Minyak Kelapa dengan Penambahan Infused Oil Bunga Kenanga - Febri Kusuma; Ngatirah; Reni Astuti Widyowanti (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2026)
The purpose of this research is to find out: (1) To find out the effect of the proportions of coconut oil and Cananga odorata on the characteristics of shampoo, (2) To find out the effect of adding Cananga odorata infused oil on the characteristics of shampoo, (3) To find out composition the proportions of coconut oil and Cananga odorata and the addition of Cananga odorata infused oil produced a shampoo with the highest preferrence score. This research uses a Complete Block Design (RBL) with two factors and two replications. The first factor is the ratio of coconut oil and cananga odorata in making cananga odorata infused oil with 3 levels, namely 120:20 grams (6:1), 160:20 grams (8:1), and 200:20 grams (10:1), while the second factor is the addition of Cananga odorata infused oil, namely 30 grams, 40 grams and 50 grams. The results showed that: (1) the proportions of coconut oil and Cananga odorata oil affected the cleaning power and aroma organoleptic, but did not affect the pH, foam stability, density, viscosity and color and texture organoleptic. (2) The addition of Cananga odorata infused oil affected the viscosity, cleaning power and color organoleptic, but did not affect the pH, foam stability, density and aroma and texture organoleptic. (3) The overall preferences for shampoo was in the neutral category for all treatments, with the highest value of 3.76 at the proportion of coconut oil and Cananga odorata 200:20 grams with the addition of 40 grams of Cananga odorata infused oil.